Effects of medium voltage electrical stimulation on initial pH decline and quality parameters during ageing and frozen storage of Nellore beef - de Alvarenga, Eloise Soares [UNESP]; Isac, Maria Fernanda [UNESP]; Rosa, Alessandra Fernandes; Silva, Saulo Luz; Nassu, Renata Tieko; Silva Barretto, Andrea Carla da [UNESP] (Elsevier, 2024)
This study aimed to evaluate the influence of medium voltage electrical stimulation (ES) at three different intensities, 200 V (Treatment 200 V, T200), 300 V (Treatment 200 V, T300), and 400 V (Treatment 400 V, T400) on the initial pH decline in post mortem muscle and the quality parameters on M. longissimus thoracis - Nellore beef, both throughout the ageing process and during frozen storage. The colour, cooking loss, and shear force parameters for samples of aged beef were determined. Additional parameters, like thaw loss, pH, and lipid oxidation were also analyzed for the frozen storage. The shear force and cooking loss decreased and colour parameters increased in Nellore beef ES compared with CON on ageing time (14 days). At frozen storage, quality parameters like pH, a*, and b* were reduced over time, and no negative effect on lipid oxidation was found. Electrical stimulation at 200 V demonstrated effectiveness for decreasing shear force to Nellore beef (M. longissimus thoracis) during frozen storage. The application of medium voltage electrical stimulation can contribute to improved quality and tenderness in Nellore beef, both during ageing and frozen storage conditions.
Keywords: Colour; Cooking loss; Lipid oxidation; Medium-voltage electrical stimulation; Shear force; Thaw loss